Lipopolysaccharide from Rhodobacter sphaeroides (TLR4 antagonist) attenuates hypersensitivity and modulates nociceptive factors. (1st January 2018) - Jurga, Agnieszka M.; Rojewska, Ewelina; Makuch, Wioletta; Mika, Joanna
Abstract: Context: Accumulating evidence has demonstrated that Toll-like receptors (TLRs), especially TLR4 localized on microglia/macrophages, may play a significant role in nociception. Objective: We examine the role of TLR4 in a neuropathic pain model. Using behavioural/biochemical methods, we examined the influence of TLR4 antagonist on levels of hypersensitivity and nociceptive factors whose contribution to neuropathy development has been confirmed. Materials and methods: Behavioural (von Frey's/cold plate) tests were performed with Wistar male rats after intrathecal administration of a TLR4 antagonist (LPS-RS ULTRAPURE (LPS-RSU), 20 μG: lipopolysaccharide from Rhodobacter sphaeroides, InvivoGen, San Diego, CA) 16 H and 1 h before chronic constriction injury (cci) to the sciatic nerve and then daily for 7 d. three groups were used: an intact group and two cci-exposed groups that received vehicle or LPS-RSU. tissue [spinal cord/dorsal root ganglia (DRG)] for western blot analysis was collected on day 7. Results: The pharmacological blockade of TLR4 diminished mechanical (from ca. 40% to 16% that in the INTACT group) and thermal (from ca. 51% to 32% that in the INTACT group) hypersensitivity despite the enhanced activation of IBA-1-positive cells in DRG. Moreover, LPS-RSU changed the ratio between IL-18/IL-18BP and MMP-9/TIMP-1 in favour of the increase of antinociceptive factors IL-18BP (25%-spinal; 96%-DRG) and TIMP-1 (15%-spinal; 50%-DRG) and additionally led to an increased IL-6 (40%-spinal; 161%-DRG), which is known to have analgesic properties in neuropathy. Conclusions: Our results provide evidence that LPS-RSU influences pain through the expression of TLR4. TLR4 blockade has analgesic properties and restores the balance between nociceptive factors, which indicates its engagement in neuropathy development.